Priority Directions and Strategic Prospects for Improving the System of Supporting Business Entities through the Attraction of Financial and Credit Resources - Zaynalov, Jahongir; Malikov, Elbek (Journal of Economics and Tourism Research, 2026)
This study analyzes the mechanisms for supporting business entities through financial and credit resources, which are an important factor of economic growth in a market economy. Its relevance is associated with the need to ensure the stability of small and medium-sized businesses, meet the demand for credit resources, and introduce digital financial technologies in the process of modernizing Uzbekistan’s economy. The research examines the theoretical foundations of attracting financial and credit resources, the current state, and ways to improve the system. According to the results, the widespread use of digital tools such as fintech and online scoring, as well as the liberalization of credit policy, contributes to increasing entrepreneurial activity.